UTILIZATION OF GAP MODEL IN PROVIDING OF SERVICES IN THE RAILWAY FREIGHT TRANSPORT (Perner's Contacts, 2013)
The contribution describes in detail the GAP model and its use in railway freight transport. Contribution points on five basic gaps in the quality of transport services, which are provided by railway undertaking. This paper contains the partial result of research which was implemented in Railway company Cargo Slovakia, a.s.. The paper is supported by the VEGA Agency by the Project 1/0188/13 „Quality factors of integrated transport system in the effective provision of public transport services in the context of globalisation “, that is solved at Faculty of Operations and Economics of Transport and Communication, University of Žilina.